Incidence of postpartum haemorrhage in women receiving therapeutic doses of low-molecular-weight heparin: results of a retrospective cohort study. Issue 2 (14th November 2011) - Roshani, Sara; Cohn, Danny M; Stehouwer, Alexander C; Wolf, Hans; van der Post, Joris A M; Büller, Harry R; Kamphuisen, Pieter W; Middeldorp, Saskia
Abstract : Background: Low-molecular-weight heparin (LMWH) is the drug of choice to prevent venous thrombosis in pregnancy, but the optimal dose for prevention while avoiding bleeding is unclear. This study investigated whether therapeutic doses of LMWH increase the incidence of postpartum haemorrhage (PPH) in a retrospective controlled cohort. Methods: All pregnant women who received therapeutic doses of LMWH between 1995 and 2008 were identified in the Academic Medical Center, Amsterdam, The Netherlands. The controls were women registered for antenatal care in the same hospital who did not use LMWH during pregnancy, matched by random electronic selection for age, parity and delivery date to LMWH users. The incidence of PPH (blood loss >500 ml), severe PPH (blood loss >1000 ml) and median blood loss were compared in two cohorts of LMWH users and non-users. Results: The incidence of PPH was 18% in LMWH users (N=95) and 22% in non-users (N=524) (RR 0.8; 95% CI 0.5 to 1.4). The incidence of severe PPH was 6% in both groups (RR 1.2; 0.5 to 2.9). The median amount of blood loss differed only in normal vaginal deliveries. It was 200 ml in LMWH users and 300 ml in non-users (difference −100 ml; 95% CI −156 to −44). Conclusion: Therapeutic doses of LMWH in pregnancy were observed not to be associated with a clinically meaningful increase in the incidence of PPH or severe PPH in women delivered in this hospital, although this observation may be confounded by the differential use of strategies to prevent bleeding. A randomised controlled trial is necessary to provide a definite answer about the optimal dose of LMWH in pregnancy.